Risk factors for fever in the neurologic intensive care unit. - Commichau, Christopher; Scarmeas, Nikolaos; Mayer, Stephan A (Neurology, 2003)
OBJECTIVE: To identify risk factors for fever among patients treated in a neurologic intensive care unit (NICU). METHODS: The authors prospectively studied the frequency and causes of fever, defined as a patient's first temperature > or =101 degrees F (38.3 degrees C), among 387 patients consecutively admitted to their NICU. After identifying risk factors for 1) any fever, 2) infectious fever, and 3) unexplained fever using logistic regression, they calculated disease-specific adjusted odds ratios for developing these types of fever among 12 diagnostic groups. RESULTS: Fever occurred in 23% (87/387) of patients. Fifty-two percent of fevers were explained by infection (predominantly pneumonia or bronchitis), and 28% were unexplained despite a complete diagnostic evaluation. NICU length of stay was a risk factor for all three types of fever (all p < 0.004); other risk factors included depressed level of consciousness for any fever (p = 0.005) and infectious fever (p = 0.048), endotracheal intubation for infectious fever (p = 0.01), and intraventricular catheterization for unexplained fever (p = 0.004). Subarachnoid hemorrhage increased the risk of both infectious and unexplained fever, even after adjusting for these risk factors (p = 0.006). CONCLUSION: Fever occurs in nearly 25% of NICU patients, and is associated with increased length of stay and depressed level of consciousness. Endotracheal intubation is a risk factor for infectious fever, whereas intraventricular catheterization is a risk factor for unexplained fever, which suggests a role for ventricular hemorrhage in the pathogenesis of "central" fever. Subarachnoid hemorrhage increases the risk of developing fever of all types.
Keywords: Adolescent; Adult; Aged; Aged, 80 and over; Brain Diseases; Bronchitis; Cerebrospinal Fluid Shunts; Comorbidity; Female; Fever; Fever of Unknown Origin; Hospital Mortality; Humans; Infection; Intensive Care Units; Intubation, Intratracheal; Length of Stay; Logistic Models; Male; Middle Aged; Neurosurgical Procedures; New York City; Pneumonia; Prospective Studies; Risk Factors; Subarachnoid Hemorrhage